Two-layer reading positions in comments on online news discourse about China. Issue 5 (October 2019) - He, Juan
Reading experience is viewed as 'interactive and negotiable' for different reading positions are created in readers' responses to the same news report. To understand the differences between ' preferred reading ' and actual readings, this article, drawing on the context models and the Appraisal framework, analyzes 785 readers' comments attached to 23 hard news stories sourced from the China Daily mobile application (APP) and the People's Daily Online website. The study combines corpus semantic tagging analysis for readers' choices of evaluative lexis with a manual analysis of Appraisal resources for reading position construction based on a whole text perspective. The results show that readers are likely to use Appraisal resources strategically to defend their own opinions against other commenters or affiliate with large numbers of potential readers without commenting. Furthermore, comments were found to be directed either at the text or at other commenters, and through this a number of different reading positions were revealed. The readers' context models are the cognitive link between discourse properties and social strategies in the process of news understanding.